Bilateral Absence of Frontal Sinus and Unilateral Mandibular Hypoplasia A Case report (Bangladesh Journal of Dental Research & Education, 2015)
Absence of frontal sinus is usually associated with various syndromes such as craniosynostosis, osteodysplasia, down syndrome etc. Geographically, absence of frontal sinus is seen usually in areas with cold climate. This paper reports a case of 18-year old Indian woman suffering from bilateral absence of frontal sinuses which was non-syndromic in conjunction with unilateral mandibular hypoplasia. The paper also highlights the clinical significance of frontal sinus which was non-syndromic absence and its rarity in warm climate such as in South East Asian regions and the treatment options of unilateral mandibular hypoplasia. DOI: http://dx.doi.org/10.3329/bjdre.v5i1.22459 Bangladesh Journal of Dental Research and Education Vol.5(1) 2015: 29-32